2022
DOI: 10.1007/s10722-022-01478-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of agro-morphological traits, seed characterization and genetic diversity of local rice (Oryza sativa L.) varieties of Pakistan

Abstract: Background: Broad base genetic diversity is essential for a sustainable crop yield to provide tolerance against biotic and abiotic stresses. In Pakistan, rice is ranked second as a staple food and cultivated under different climatic zones. However, very little is known in terms of rice genetic diversity.Methods and results: Present research were performed to evaluate the genetic diversity among 12 local rice varieties by using 5 SSR markers. Furthermore, agro-morphological parameters and seed characterization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…They found the positive correlation (0.62) for filled grain number and negative and significant correlation for the unfilled grain number with grain yield (-0.47*). Therefore, the grain yield is increased by increasing the number of filled grains and decreasing the number of empty grains per panicle which was noticed earlier by Parida et al (2022) and Fazal et al (2022). Not only the panicle length but also the filled grain number and 1000 grain weight also important determining traits for improving grain yield.…”
Section: Results and Discussion Performance Evaluation For Quantitati...mentioning
confidence: 84%
See 1 more Smart Citation
“…They found the positive correlation (0.62) for filled grain number and negative and significant correlation for the unfilled grain number with grain yield (-0.47*). Therefore, the grain yield is increased by increasing the number of filled grains and decreasing the number of empty grains per panicle which was noticed earlier by Parida et al (2022) and Fazal et al (2022). Not only the panicle length but also the filled grain number and 1000 grain weight also important determining traits for improving grain yield.…”
Section: Results and Discussion Performance Evaluation For Quantitati...mentioning
confidence: 84%
“…Hybrid rice has the capability to increase almost 20-30% more yield than high yielding varieties (HYV) and traditional rice varieties (Fazal et al, 2022;Hossain et al, 2017;Yesmin et al, 2022). In the last two decades, much emphasis has been given to cultivate hybrid rice for the improvement rice production in Bangladesh (Azad et al, 2022;Hasan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The plant architecture traits, namely, PH, CL, FLL, FLW, PdL, and PL, showed a high extent variation between and within landrace accessions. In previous studies, phenotypic variation in plant traits was reported in the landraces and improved cultivars of aromatic rices (Akhtar et al, 2022;Fazal et al, 2023). Chakravorty et al (2013, Islam, Akter, et al (2018), Mathure et al (2011), andS.…”
Section: Crop Sciencementioning
confidence: 99%
“…In our study, plant architecture traits like plant height, culm length, flag-leaf length and width, peduncle length and panicle length showed high extent of morphological variation between and within landraces accessions. In previous studies, phenotypic variation in plant traits were reported in both aromatic rice landraces and improved cultivars (Mathure et al 2011;Roy et al 2016;Islam et al 2018a,b;Akhtar et al 2022;Fazal et al 2023). Chakravorty et al (2013) analyzed diversity of 18 agro-morphological traits in 51 landraces of aromatic and non-aromatic rices of West Bengal and reported high variation for plant height, culm length, leaf length and width and panicle length.…”
Section: Morphological Variability In Aromatic Rice Landracesmentioning
confidence: 99%